Children's work in environmental chores: 'says who?'. (2nd January 2023) - DeGraff, Deborah S.; Levison, Deborah; Dungumaro, Esther
ABSTRACT: The standard approach for collecting sociodemographic data about children in developing countries is to elicit information from adults. While using proxy respondents is appropriate for very young children or for questions likely beyond children's knowledge, it is less clear that it is better for older children and topics within their experience. Several arguments can be made that children could provide better or equally valid information on their activities than proxy respondents. We explore this question in the context of children's work on environmental chores in rural Tanzania, using data that include parallel questions to children ages 10–17 and to proxy respondents about those children. Given the paucity of research on this issue, we offer exploratory evidence suggesting that efforts to collect data directly from children are fruitful and should be vigorously pursued, in keeping with Article 12 of the United Nations Convention on the Rights of the Child